2017
DOI: 10.12705/665.7
|View full text |Cite
|
Sign up to set email alerts
|

Multi‐locus phylogeny of Ludwigia (Onagraceae): Insights on infra‐ generic relationships and the current classification of the genus

Abstract: Ludwigia (Onagraceae) is a worldwide wetland genus with 83 species currently classified as members of 23 sec­ tions. Past studies have documented the morphological diversity and complex evolutionary history. Here we provide the first comprehensive molecular phylogeny of Ludwigia, using our new data to examine the existing evolutionary hypotheses. We employed both nuclear (ITS, waxy) and chloroplast (rps16, rpl16, trnL‐trnF, trnL‐CD, trnG) DNA regions for this study. Our results suggest that the North Temperate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

11
53
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(73 citation statements)
references
References 93 publications
(143 reference statements)
11
53
0
2
Order By: Relevance
“…Several recent studies have shown that combining both molecular and cytological analyses provides even better resolution to untangle the evolutionary puzzle in polyploid and/or reticulate groups (Lipman et al, 2013;Mandák et al, 2018). Ludwigia L., the sole genus in Onagraceae subfamily Ludwigioideae, is an intensively studied polyploid complex comprising 83 predominately wetland species with a worldwide distribution (Munz, 1942;Raven, 1963;Eyde, 1977;Raven & Tai, 1979;Peng, 1983;Wagner et al, 2007;Pesamosca & Boldrini, 2015;Liu et al, 2017). The North Temperate haplostemonous (NTH) Ludwigia group, characterized by 4-merous and haplostemonous flowers and north-temperate distribution, includes 24 species that have been classified in section Ludwigia, section Isnardia (L.) W. L. Wagner & Hoch, section Microcarpium Munz, and section Miquelia P. H. Raven (Table 1; Raven, 1963;Wagner et al, 2007).…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…Several recent studies have shown that combining both molecular and cytological analyses provides even better resolution to untangle the evolutionary puzzle in polyploid and/or reticulate groups (Lipman et al, 2013;Mandák et al, 2018). Ludwigia L., the sole genus in Onagraceae subfamily Ludwigioideae, is an intensively studied polyploid complex comprising 83 predominately wetland species with a worldwide distribution (Munz, 1942;Raven, 1963;Eyde, 1977;Raven & Tai, 1979;Peng, 1983;Wagner et al, 2007;Pesamosca & Boldrini, 2015;Liu et al, 2017). The North Temperate haplostemonous (NTH) Ludwigia group, characterized by 4-merous and haplostemonous flowers and north-temperate distribution, includes 24 species that have been classified in section Ludwigia, section Isnardia (L.) W. L. Wagner & Hoch, section Microcarpium Munz, and section Miquelia P. H. Raven (Table 1; Raven, 1963;Wagner et al, 2007).…”
mentioning
confidence: 99%
“…Recent phylogenetic study focused on Ludwigia strongly (chloroplast [cp] DNA) or moderately (nuclear [nr] DNA) supports that section Ludwigia and the Microcarpium complex are sister clades (Liu et al, 2017). Liu et al (2017) also found that neither section Isnardia nor section Microcarpium is monophyletic.…”
mentioning
confidence: 99%
See 3 more Smart Citations